Analisis Struktur Batin Dan Makna Pada Puisi “ENGKAU” Karya Muhammad Zuhri - Ardhitya Akbhar Praya; Rivaldi Saputra (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The material object of this study is Engkau poetry by Muhammad Zuhri, while the formal object is semiotics by Riffaterre. In his theory, Michael Riffaterre, introduces two level of reading, i.e. heuristics (mimetic reading, based on the dictionary meaning, characterized by non-gramatical) and hermeneutic reading or retroactive reading (reading decoding process by searching models, matrix, hipogram: actual and potential to get a unity of meaning). The result of this study revealed that Engkau poetry in heuristics reading has not been found its unity of meaning, and it is still scattered and fragmented. In hermeneutic or retroactive reading, potential hipogram depicts the inner journey of the “Aku” lyrics from stagnant stage to the finding of bright spot stage. There are two monumental models in Engkau poetry.